A two-color fluorescence enhanced dot-blot assay for revealing co-operative expression of chemokine receptors in cells. Issue 7 (8th January 2018) - Khan, Naseer Ullah; He, Hua; Wang, Xiaojuan; Ge, Baosheng; Wang, Qian; Liu, Xu; Lao, Jun; Wang, Yanan; Li, Jiqiang; Wang, Zhencai; Zhou, Shitan; Huang, Fang
Abstract : A highly sensitive two-color dot-blot assay has been developed to simultaneously detect co-operative expression of chemokine receptors in cells. Abstract : An ultra-high fluorescence enhancement for two dyes on photonic crystal films was achieved to construct a two-color immuno-dot blot assay. This assay was demonstrated to simultaneously detect chemokine receptor co-expressed in cancer cells and reveal their co-operative and subtle changes after binding with respective ligands and drugs.